2016
DOI: 10.1093/mnras/stw2279
|View full text |Cite
|
Sign up to set email alerts
|

The motion of chondrules and other particles in a protoplanetary disc with temperature fluctuations

Abstract: We consider the mechanism of photophoretic transport in protoplanetary disks that are optically thick to radiation. Here, photophoresis is not caused by the central star but by temperature fluctuations that subject suspended solid particles, including chondrules, to non-isotropic thermal radiation within the disk. These short-lived temperature fluctuations can explain time-of-flight size sorting and general number density enhancements. The same mechanism will also lead to velocity fluctuations of dust aggregat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…In protoplanetary disks, millimeter-sized particles usually collide at velocities below 1 m/s (Blum and Wurm, 2008). Their collision velocity might be increased one way or the other through the shocks, gas expansion or photophoresis, especially after a melting event (Wurm and Haack, 2009;Wurm et al, 2010;Loesche et al, 2016). It has generally been taken for granted that chondrules that collide at hot temperatures stick together even at collision velocities of 1 m/s (Kring, 1991;Ciesla et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In protoplanetary disks, millimeter-sized particles usually collide at velocities below 1 m/s (Blum and Wurm, 2008). Their collision velocity might be increased one way or the other through the shocks, gas expansion or photophoresis, especially after a melting event (Wurm and Haack, 2009;Wurm et al, 2010;Loesche et al, 2016). It has generally been taken for granted that chondrules that collide at hot temperatures stick together even at collision velocities of 1 m/s (Kring, 1991;Ciesla et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Particle transport therefore either occurs in the inner part (gap) of the disc, or over the surface of the disk, albeit more effectively (Wurm & Haack 2009) than radiation pressure. However, thermal radiation in a disk with temperature fluctuations or radiation from a forming planet also induces photophoretic motion, which can lift and trap particles and might be important for chondrules being transported after they form (van Eymeren & Wurm 2012;Teiser & Dodson-Robinson 2013;Loesche et al 2016b;McNally & McClure 2017). Overall, photophoresis has been put on firm ground in recent years by experiments, and analytical models have been derived based on these experiments.…”
Section: Particle Transportmentioning
confidence: 99%
“…The problem with the optical thick inner part of protoplanetary disks might be bypassed by moving grains over the optical thin surface [107,108]. However, direct stellar radiation might not be the sole driver for photophoresis, e.g., Loesche et al [109] showed that temperature fluctuations, e.g., those witnessed by chondrule formation, lead to efficient photophoretic forces. McNally and Hubbard [110] investigated photophoresis in more detail in dense environments .…”
Section: Photophoresismentioning
confidence: 99%